2018
DOI: 10.1371/journal.pone.0207458
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal justice climate, extra-role performance and work family balance: A multilevel mediation model of employee well-being

Abstract: The global economic recession is relevant in public administration, especially in terms of the human factor. If we pretend to empower people as a resource, a key aspect is the perception of equity in their relationships. Previous research has shown how a positive shared interpersonal justice climate (IJC) in a work team impacts employee well-being, affecting the level of engagement and burnout. This influence is crucial in achieving positive results in the organization and for employees. The objective was to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Work-family balance has been emphasized and proven to be associated with burnout. 17,35 Social support including family support has been investigated and validated to interfere with provider burnout. 36,37 Female physicians burdened with high risk pregnancies and miscarriages tend to experience higher burnout rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work-family balance has been emphasized and proven to be associated with burnout. 17,35 Social support including family support has been investigated and validated to interfere with provider burnout. 36,37 Female physicians burdened with high risk pregnancies and miscarriages tend to experience higher burnout rates.…”
Section: Discussionmentioning
confidence: 99%
“…Family support seems to be another provider wellness culture domain that could potentially protect against provider burnout. Work-family balance has been emphasized and proven to be associated with burnout [ 17 , 35 ]. Social support including family support has been investigated and validated to interfere with provider burnout [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological climates Global Im et al 2018Cohesion Positive affect Task and contextual Pecino et al (2018).…”
Section: High-performance Work Systemsmentioning
confidence: 99%
“…Lucas et al [ 29 ] found that the justice climate could strengthen the associations between individual-level justice perceptions and personal well-being. In Pecino et al [ 32 ], interpersonal justice climate in a work team was significantly associated with well-being indicators (burnout and engagement) and work outcomes (work family balance and extra-role performance). Employees work in a department with poor justice climate reported more somatic complaints [ 33 ].…”
Section: Introductionmentioning
confidence: 99%